Transformasi Nilai-Nilai Islam dalam Kurikulum Pendidikan Modern - Asmuni, Hadiqoh (MOMENTUM : Jurnal Sosial dan Keagamaan, 2025)
In contemporary educational curricula, the transformation of Islamic values represents a strategic effort to integrate religious principles into formal education. Schools must preserve their religious identity while preparing students to face the challenges of globalization and rapid technological advancement. This study investigates how Islamic values can be incorporated and implemented within the curriculum to develop a generation that is not only academically intelligent. Islam also emphasizes the importance of building strong and noble character as the fundamental basis for living a meaningful life. This research examines several curriculum models that have successfully integrated Islamic values. The study employs a qualitative approach. The findings reveal that applying principles such as justice, tolerance, and cooperation into learning activities can enhance students’ motivation and desire to learn. Moreover, the success of this transformation greatly depends on collaboration between educators, parents, and the community. Therefore, a curriculum grounded in Islamic values not only provides students with education but also teaches them good ethics and morality. According to this study, existing curricula should be modified and innovated to align with contemporary developments while maintaining the core values of Islamic teachings. Thus, Islamic education can serve as a strong foundation for shaping the character of future generations who are faithful and honest.